Associations of GPCR autoantibodies with clinical, histological, metabolic and hemodynamic features in non-ischemic heart failure patients. (3rd October 2022) - Karschnia, M; Zweck, E; Scheiber, D; Heidecke, H; Barthuber, C; Kelm, M; Roden, M; Westenfeld, R; Szendroedi, J; Boege, F
Abstract: Background: Roughly one third of cases of chronic heart failure (HF) are caused by genetic predisposition, metabolic stress and cardiac inflammation. Animal studies suggest that heart-reactive autoantibodies, most notably those directed against G-protein-coupled receptors (GPCR), could also play a pathogenetic role in the disease. However, so far, a causal link between humoral GPCR-autoimmunity and human non-ischemic heart failure other than Chagas' cardiomyopathy remains unclear. Purpose: Here, we investigated possible associations of GPCR autoantibodies with inflammatory, hemodynamic, metabolic and functional parameters in patients with chronic non-ischemic HF unrelated to Chagas' disease. Methods: We prospectively included 95 patients with newly diagnosed non-ischemic heart failure of unknown origin. Basic cardiac characterization comprised transthoracic echocardiography, cardiac magnetic resonance imaging, coronary angiography and right heart catheterization with endomyocardial biopsy. Mitochondrial oxidative phosphorylation capacity and coupling was measured using high-resolution respirometry in permeabilized myocardial fibers. A panel of candidate GPCR-autoantibodies was determined by validated and certified immune-assays in peripheral venous blood of the HF-patients and 60 matched healthy individuals. Results were normalized to total IgG. Results: Among 10 candidate GPCR-autoantibodies determined, only autoantibodies for α1-adrenergic receptor (α1AR), β1-adrenergic receptor (β1AR), muscarinic receptor M5 (M5AR), angiotensin II receptor type 1 (AT1R) and type 2 (AT2R) exhibited HF-associated alterations: Autoantibodies against β1AR, M5R and AT2R were increased. Autoantibodies against α1AR and AT1R were decreased (Figure). These alterations were significant (p<0.01), but not, or only weakly, correlated with markers of cardiac inflammation, cardiac damage, hemodynamics, endomyocardial histology or left ventricular inflammation judged by T2-mapping. However, in HF-patients, increased AT2R autoantibodies were associated with improved myocardial mitochondrial coupling (r=−0.27, p=0.021), and decreased AT2R autoantibodies were associated with insulin resistance (r=−0.24 p=0.027). Conclusion(s): Some previously postulated alterations of GPCR autoantibodies were confirmed in thoroughly characterized HF-patients. However, association of these alterations with cardiac function was not traceable, which argues against a specific pathogenic role. Our data are compatible with multifaceted interactions of GPCR-autoantibodies with the myocardium and potentially with glucose metabolism, possibly indicating a disease-modifying or compensatory role. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Research comission of the Heinrich-Heine University Duesseldorf